MEKANISME TATA KELOLA PERUSAHAAN DAN AUDIT REPORT LAG - Rezaldy Adhyasa; Totok Dewayanto (Diponegoro Journal of Accounting, 2020)
The purpose of this study is to examine the role of corporate governance in the delay of audit reports. The population in this study consisted of all manufacturing companies on the Indonesia Stock Exchange for the period 2015 - 2017. Sampling was conducted using a purposive sampling method. The total sample of this research is 243 companies.            This study uses multiple regression analysis for hypothesis testing. The results of this study indicate that the size of the audit committee, the type of auditor, company performance, and the number of board meetings have a negative and significant effect on ARL. Meanwhile, the independence of the board and the number of audit committee meetings had a significant positive effect on ARL. Audit committee qualifications do not affect the audit report lag level.